Clinical presentations leading to arrhythmogenic left ventricular cardiomyopathy. Issue 1 (20th April 2022) - Graziosi, Maddalena; Ditaranto, Raffaello; Rapezzi, Claudio; Pasquale, Ferdinando; Lovato, Luigi; Leone, Ornella; Parisi, Vanda; Potena, Luciano; Ferrara, Valentina; Minnucci, Matteo; Caponetti, Angelo Giuseppe; Chiti, Chiara; et al.
Abstract : Objectives: To describe a cohort of patients with arrhythmogenic left ventricular cardiomyopathy (ALVC), focusing on the spectrum of the clinical presentations. Methods: Patients were retrospectively evaluated between January 2012 and June 2020. Diagnosis was based on (1) ≥3 contiguous segments with subepicardial/midwall late gadolinium enhancement in the left ventricle (LV) at cardiac magnetic resonance plus a likely pathogenic/pathogenic arrhythmogenic cardiomyopathy (AC) associated genetic mutation and/or familial history of AC and/or red flags for ALVC (ie, negative T waves in V4-6/aVL, low voltages in limb leads, right bundle branch block like ventricular tachycardia) or (2) pathology examination of explanted hearts or autoptic cases suffering sudden cardiac death (SCD). Significant right ventricular involvement was an exclusion criterion. Results: Fifty-two patients (63% males, age 45 years (31–53)) composed the study cohort. Twenty-one (41%) had normal echocardiogram, 13 (25%) a hypokinetic non-dilated cardiomyopathy (HNDC) and 17 (33%) a dilated cardiomyopathy (DCM). Of 47 tested patients, 29 (62%) were carriers of a pathogenic/likely pathogenic DNA variant. Clinical contexts leading to diagnosis were SCD in 3 (6%), ventricular arrhythmias in 15 (29%), chest pain in 8 (15%), heart failure in 6 (12%) and familial screening in 20 (38%). Thirty patients (57%) had previously received a diagnosis other than ALVC with a diagnostic delay of 6 years (IQR 1–7). Conclusions: ALVC is hidden in different clinical scenarios with a phenotypic spectrum ranging from normal LV to HNDC and DCM. Ventricular arrhythmias, chest pain, heart failure and SCD are the main clinical presentations, being familial screening essential for the affected relatives' identification.